The Role of IoT Solutions in Transforming Mobility in Transport Sector - wachira, David; Chege, Amos; Mwadulo, Mary; Bundi, Dorothy (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
The potential of Internet of Things technology to enhance transport sector efficiency and effectiveness has been recognized in public transportation authorities. However, its adoption in public transport industry has remained underutilized. This study looks into how IoT may improve safety, sustainability, and efficiency in traffic management, and public transportation. A mixed-methods approach will be taken, with both quantitative and qualitative data collected and analyzed. Quantitative methods will include surveys aimed at a diverse target population, including government agencies in charge of transportation infrastructure and policy, three transportation-related businesses in Meru and citizens who use transportation services on a regular basis. The adoption of IoT is expected to yield significant improvements across various aspects of transportation. Traffic management will witness a remarkable transformation, with projections suggesting that 75% of respondents anticipate a reduction in congestion and 60% expect a boost in public transportation efficiency. To identify best practices and lessons gained, qualitative approaches will use interviews with selected three Transport industry managers, and six drivers . The study will quantify the influence of IoT on traffic flow, and public transportation efficiency, by statistically analyzing survey data and making estimates based on existing IoT adoption trends. This will provide measurable evidence of predicted benefits. A thorough evaluation of existing research will look into the design and implementation of IoT-based monitoring models, emphasizing IoT’s disruptive potential in the transportation industry. The study will contribute to the development of robust and interoperable transport monitoring systems by investigating the integration of sensors, connection technologies, and data analytics, which are the foundations of IoT technology. The findings will assist in directing the integration of IoT in public service vehicles, creating the way for a future of safe, efficient, and sustainable transportation.